Clive Cussler Condor's fury [large type] : a novel from the NUMA files - Cussler, Clive; Brown, Graham, 1969- (Cussler, Clive. Kurt Austin adventures., 2023)
"On a NUMA training mission in the Caribbean, Kurt Austin and Joe Zavala catch a distress call from a nearby freighter. Leaping into action, they locate a damaged vessel and a dead captain clutching a shotgun. While searching the freighter for clues, Kurt and Joe are ambushed by crew members who seem terrified and disoriented, almost brainwashed. The trawler they were hauling has vanished, taken--the men say--by baffling lights that circled the ship. Kurt and Joe deduce that the men are suffering from Havana Syndrome, which deepens the mystery and raises the stakes. Soon, they're confronting Cuban mercenaries who plan to use magnificent modern airships to hijack a nuclear submarine--culminating in a life-or-death showdown in the skies"--Back cover.